The The Jigsaw Model Strategy As A Peer-Teaching Method In Islamic Education Subjects - Rihadatul Aisy, Salwa; Syahidin (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
The Jigsaw Model, which emphasizes collaboration among students, provides an opportunity for them to become "experts" in a particular subject and teach it to their peers. This strategy enhances students' understanding of the material and develops their social and communication skills. This study investigates the implementation of the Jigsaw model strategy as a peer-teaching method in Islamic Religious Education (PAI) subjects, focusing on its potential to integrate cognitive learning with spiritual and moral development. Using a descriptive qualitative approach and library research method, this article highlights the benefits and challenges of applying the Jigsaw model in PAI learning. Key findings reveal that the Jigsaw model not only reinforces mastery of the subject matter but also fosters communication skills, social responsibility, and cooperation among students. Moreover, the strategy significantly contributes to creating a dynamic and interactive learning environment that aligns with Islamic educational values. This study offers a novel perspective by demonstrating how the Jigsaw model bridges academic achievement and character formation, providing valuable insights for educators seeking to enhance collaborative and values-based learning practices.